Electrostatic scattering by strips - E. Danicki (Archives of Acoustics)
A system of in-plane periodic perfectly conducting strips is considered embedded in an preexisting electric field which, in applications, can result from propagation of an elastic wave in a piezoelectric material supporting strips on its surface. The spatial spectrum of charge distribution in the plane of strips is of our primary interest. In spite of the functional dependence between the spectrum and the spatial distribution of charge by means of the Fourier transform, its direct application leads to a considerable numerical error caused by poor numerical representation of the singular field at the strip edges. Carrying out the analysis in the spectral domain instead of direct evaluation of the spatial charge distribution overcomes this difficulty.